2014
DOI: 10.3389/fpubh.2014.00281
|View full text |Cite
|
Sign up to set email alerts
|

Patient Reported Delays in Seeking Treatment for Tuberculosis among Adult and Pediatric TB Patients and TB Patients Co-Infected with HIV in Lima, Peru: A Qualitative Study

Abstract: Introduction: Tuberculosis (TB) remains a significant public health challenge worldwide, and particularly in Peru with one of the highest incidence rates in Latin America. TB patient behavior has a direct influence on whether a patient will receive timely diagnosis and successful treatment of their illness.Objectives: The objective was to understand the complex factors that can impact TB patient health seeking behavior.Methods: In-depth interviews were conducted with adult and parents of pediatric patients rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 26 publications
2
34
0
1
Order By: Relevance
“…Indeed, inadequate knowledge about TB and stigma has previously been associated with longer diagnostic delays [3, 23, 3335]. In contrast, studies from Georgia, Ethiopia and Angola reported that the use of antibiotics prior to TB diagnosis was associated with a prolonged delay [5, 36, 37]. This difference can be explained by the fact that we defined use of medication as any medication prior to TB diagnosis, rather than antibiotics alone, as patients may not accurately remember the type of medication used in the past.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, inadequate knowledge about TB and stigma has previously been associated with longer diagnostic delays [3, 23, 3335]. In contrast, studies from Georgia, Ethiopia and Angola reported that the use of antibiotics prior to TB diagnosis was associated with a prolonged delay [5, 36, 37]. This difference can be explained by the fact that we defined use of medication as any medication prior to TB diagnosis, rather than antibiotics alone, as patients may not accurately remember the type of medication used in the past.…”
Section: Discussionmentioning
confidence: 99%
“…There may be several reasons for this but one possibility is that TB disease remains undiagnosed in household adult contacts. Household contacts may avoid visiting health care facilities because of the stigma associated with TB diagnosis and/or the fear that they may be co-infected with HIV [ 17 , 18 ]; alternatively, health care providers may fail to diagnose TB disease in household suspects [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…This great demand for self-medication is explained by a qualitative study developed in Peru, which points out that TB patients tend to assume that the initial symptoms are not serious and could therefore be treated with symptomatic drugs purchased in a drug store. Commonly, these people did not seek medical diagnosis until the symptoms were severe or debilitating (23) . Therefore, self-medication becomes a determining factor in the delay in the search for health care.…”
Section: Discussionmentioning
confidence: 99%